2015
DOI: 10.1094/pdis-05-14-0519-re
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of a Tuber Rot and Foliar Blight of Potato Caused by Phytophthora nicotianae

Abstract: Taylor, R. J., Pasche, J. S., and Gudmestad, N. C. 2015. Etiology o f a tuber rot and foliar blight of potato caused by Phytophthora nicotianae. Plant Dis. 99:474-481. Although Phytophthora nicotianae is not normally considered to be an important pathogen of potato (Solanum tuberosum), intermittent out breaks o f a foliar blight and tuber rot have been reported in the United States over the past 75 years. Due to the sporadic nature of these reports, little is known about the etiology o f the disease in potato.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Previous studies have indicated that P. nicotianae can cause potato tuber rot and eggplant fruit rot. Symptoms of potato infection were characterised as black spots with brown edges, and eggplants were infected with brown and sunken circle spots (Taylor et al 2015;Garcia-Estrada et al 2020). Potatoes and eggplants were selected as experimental materials for inoculation trials, having the same maturity, similar size, disease-free, and uniform weight (110 ± 10 g).…”
Section: In Vivo Antifungal Activity Testmentioning
confidence: 99%
“…Previous studies have indicated that P. nicotianae can cause potato tuber rot and eggplant fruit rot. Symptoms of potato infection were characterised as black spots with brown edges, and eggplants were infected with brown and sunken circle spots (Taylor et al 2015;Garcia-Estrada et al 2020). Potatoes and eggplants were selected as experimental materials for inoculation trials, having the same maturity, similar size, disease-free, and uniform weight (110 ± 10 g).…”
Section: In Vivo Antifungal Activity Testmentioning
confidence: 99%